Attempt To Reducing The Ground Vibration Level Due To Blasting Activity Based On The Evaluation Of Blasting Geometry - Bunyam, Timothy Lambat (Universiti Sains Malaysia, 2018)
Ground vibration result from blasting activity at Penjom Gold Mine has been classified as safe and secure based on the standard vibration level according to Departmen of Minerals and Geoscience of Malaysia with 0.4 mm/s – 2.39 mm/s actual PPV. However, the resident who live around the area within 1700 meters radius may still can feel the ground vibration that could damage their houses. Therefore, it required geometric design and blasting patterns which is expected to be able to reduce the level of ground vibration. The ground vibration is measured using vibrometer and expressed in peak particle velocity (PPV). The actual PPV value is required to find the SD (scaled distance) value with